Prototype of Diabetic Foot Screening Website Based on Inlow's 60-second Footscreen: An Effort to Prevent Complications in Diabetes Mellitus Patients at the Sindangwangi Community Health Center - Nadila Amanda Dwi; Bhakti Aryani; Yanto Haryanto; Fitria Dewi Rahmawati (CV. Inara, 2026)
The increasing prevalence of diabetes mellitus necessitates aggressive preventive interventions, particularly for diabetic foot ulcers that often go undetected in primary care settings. This study aimed to design and develop a web-based prototype for diabetic foot screening using Inlow's 60-second Diabetic Foot Screen integrated with a forward-chaining Clinical Decision Support System. This research employed a Research and Development approach with the Expert System Development Life Cycle framework. Data were collected from 30 patients with diabetes at Sindangwangi Health Center using purposive sampling. The system's usability was evaluated using the Post-Study System Usability Questionnaire (PSSUQ). The developed system successfully automated risk categorization and provided personalized clinical recommendations based on physical foot parameters. Usability testing revealed high satisfaction levels with a grand mean PSSUQ score of 1.34, where System Quality (1.47), Information Quality (1.41), and Interface Quality (1.15) were all rated as excellent. These findings demonstrate that the integrated digital screening tool is reliable, highly usable, and effectively facilitates early detection of foot complications in primary health services. This innovation provides a scalable solution for enhancing preventive care, reducing the burden of diabetes-related complications, and improving health documentation precision in resource-limited settings.